Administration of Lactobacillus paracasei ameliorates type 2 diabetes in mice. Issue 7 (2nd July 2018) - Dang, Fangfang; Jiang, Yujun; Pan, Ruili; Zhou, Yanhong; Wu, Shuang; Wang, Rui; Zhuang, Kejin; Zhang, Wei; Li, Tiejing; Man, Chaoxin
Abstract : Lactobacillus paracasei TD062 with high inhibitory activity ameliorated lipid metabolism, oxidative stress, glucose metabolism and the PI3K/Akt pathway in diabetic mice, and the effects were dose-dependent to some extent. Abstract : Probiotics have been proposed as an option for the prevention of type 2 diabetes mellitus (T2DM). The objective of this study was to evaluate the hypoglycemic effects of Lactobacillus paracasei on diabetic mice and explore the possible underlying molecular mechanism. The α-glucosidase inhibitory activities of eight L. paracasei strains were assessed in vitro . L. paracasei TD062 with high α-glucosidase inhibitory activity (31.9%) showed an excellent antidiabetic ability and it could survive in simulated gastrointestinal juices. To investigate the beneficial effects of L. paracasei TD062, diabetic mice were treated with the strain at 10 9, 10 8 and 10 7 CFU ml −1 . The results indicated that the administration of L. paracasei TD062 could regulate the levels of fasting blood glucose (FBG), postprandial blood glucose (PBG), glucose tolerance, hepatic glycogen and lipid metabolism. In addition, the antioxidant capacity was also improved by oral administration of L. paracasei TD062. And the hypoglycemic effects exhibited dose dependence to some extent. Furthermore, it was revealed that L. paracasei TD062 had a positive effect on the expression levels of genes related to glucose metabolism and the PI3K/Akt pathway. These results demonstrated that L. paracasei TD062 played an important role in preventing the development of T2DM and might be applied as a new type of hypoglycemic agent in functional foods.